2012
DOI: 10.1089/bfm.2011.0122
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Breastfeeding and Herbs

Abstract: Our review concludes that further research is needed to assess the prevalence, efficacy, and safety of commonly used herbs during breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 31 publications
4
51
1
Order By: Relevance
“…101 Similarly, the US Government Accountability Office found that 16 of 40 common herbal dietary supplements obtained from retail stores contained pesticide residues. 102 Safety data are lacking for many herbs commonly used during breastfeeding, such as chamomile, 103 black cohosh, 104 blue cohosh, 105 chastetree, 106 echinacea, 107 ginseng, 108 gingko, 109 Hypericum (St John' s wort), 110,111 and valerian. 112 Adverse events have been reported in both breastfeeding infants and mothers.…”
Section: Commonly Used Herbal Productsmentioning
confidence: 99%
“…101 Similarly, the US Government Accountability Office found that 16 of 40 common herbal dietary supplements obtained from retail stores contained pesticide residues. 102 Safety data are lacking for many herbs commonly used during breastfeeding, such as chamomile, 103 black cohosh, 104 blue cohosh, 105 chastetree, 106 echinacea, 107 ginseng, 108 gingko, 109 Hypericum (St John' s wort), 110,111 and valerian. 112 Adverse events have been reported in both breastfeeding infants and mothers.…”
Section: Commonly Used Herbal Productsmentioning
confidence: 99%
“…16,20 According to the Academy of Breastfeeding Medicine's clinical protocol for galactogogues, 32 "the mechanism(s) of action for most herbals are unknown. Most of them have not been scientifically evaluated, but traditional use suggests safety and possible efficacy."…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains an overall lack of evidence regarding the effectiveness, safety, and acceptability of many CAM therapies for PIM, including acupuncture, herbal supplements, and relaxation/ visual imagery techniques. [15][16][17] Despite this, herbal supplements are widely used and recommended by lactation consultants. Meditation and other cognitively based relaxation techniques have also emerged as noninvasive, potentially effective interventions for PIM affected by stress or anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Very little research exists to guide clinical use of these herbs. 17 Parsley is believed to reduce the prolactin level and could reduce the milk supply when eaten as a food, such as in tabouli. 18 Peppermint oil might reduce the milk supply when used topically.…”
Section: Herbsmentioning
confidence: 99%